Combination of synthetic and natural polymers in hydrogel: An impact on drug permeation - Gopa Roy Biswas,Sutapa Biswas Majee,Animikh Roy (Journal of Applied Pharmaceutical Science, 2016)
Topical hydrogel preparations are applied on skin to obtain local or systemic action. NSAID’s are non-steroidal drugs having excellent anti-inflammatory and analgesic activity but it produces GIT ulceration when used orally. To overcome that problem with oral formulations, many NSAID’s are preferred to be administered by topical route. The present investigation is aimed to formulate the hydrogel of Diclofenac potassium with different ratio of Carbopol of different grades along with guar gum for application over the skin. Fourier transform Infrared (FT-IR) spectrophotometer has been used to notice drug - polymer interaction. After getting satisfactory combinations of polymers, hydrogel formulations of Diclofenac potassium were subjected to different physicochemical studies. Evaluation tests for visual appearance, pH, viscosity, spreadability, swelling index etc. were found satisfactory. To investigate the drug permeation kinetics and permeability coefficient from the goat abdominal skin, pieces of goat skin were fixed on the Franz diffusion cell, in a way that the upper surface of abdominal skin faced the donor chamber. The experiment was carried out with 2 gm of the drug loaded hydrogel spreaded on the skin surface at 32 °C in phosphate buffer pH-5.8. A distinct correlation between % swelling index and permeability coefficient of the formulations through goat abdominal skin has been observed. With increase in % swelling index over a period of 8 h the permeability coefficient decreased. It indicates that swelling of hydrogel forms a sticky, gelatinous mass that retards the permeation of Diclofenac potassium through goat abdominal skin. There are significant co relations between viscosity of hydrogel, % swelling index and permeation coefficient. It has been found that with increase in viscosity, permeability coefficient increased whereas permeability coefficient of drug decreased with increase in % swelling index of the formulations.
Keywords: Hydrogel,goat abdominal skin,Spreadability,Swelling index,Viscosity,Permeability coefficient.